2009
DOI: 10.1002/ejlt.200800150
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SatSatSat and SatOSat on crystallization of model fat blends

Abstract: In this study, the crystallization and melting properties of six different fat blends with the same saturated fat content (30%) but with a varying content of trisaturated and disaturated triacylglycerols were investigated using pulsed NMR, DSC and polarized light microscopy. Blends were either palmitic (P) or stearic (S) based, and were combinations of SatSatSat-rich (Sat = saturated) and SatOSat-rich (O = oleic) vegetable oils with high-oleic sunflower oil. The DSC results suggested that PPP forms mixed cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 22 publications
3
47
0
Order By: Relevance
“…At longer isothermal times the low melting peak and exothermal peak disappeared and the high melting peak was the only remaining peak. Based on Vereecken et al (2009), this behaviour might be explained by a polymorphic transition (as indicated in Fig. 6), but to be completely sure about this, X-ray diffraction is needed.…”
Section: Waxd-analysismentioning
confidence: 99%
See 2 more Smart Citations
“…At longer isothermal times the low melting peak and exothermal peak disappeared and the high melting peak was the only remaining peak. Based on Vereecken et al (2009), this behaviour might be explained by a polymorphic transition (as indicated in Fig. 6), but to be completely sure about this, X-ray diffraction is needed.…”
Section: Waxd-analysismentioning
confidence: 99%
“…In a previous study of our group (Vereecken et al, 2009), the explanation of the mechanism of the two-step crystallization was obtained by looking at the peak maxima in the melting curves obtained from the stop-and-return experiments. Indeed, the peak maxima of the melting curves at different isothermal times will shift when there is a change of the polymorphic form or when there is fractional crystallization.…”
Section: Waxd-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the complex behavior of some fats in terms of crystallization, polymorphic transformation, crystal morphology and aggregation depends directly on the properties of their TAGs (Foubert et al, 2006;Foubert et al, 2007, De Graef et al, 2012. The effects of different tristearin (StStSt) and StOSt ratios in TAGs on the crystallization behavior of different fat blends with the same fatty acid composition has been studied (Vereecken et al, 2009). Accordingly, StStSt does not appear to exert a seeding effect on the other TAGs present in the TAG mixture, unlike fats containing tripalmitin and dipalmitoyl glycerol.…”
Section: Resultsmentioning
confidence: 99%
“…To decrease the complexity of the oil (and thereby increase the calculation speed), the number of TAG was reduced by lumping them into groups, using two criteria: First, one TAG from every TAG-category (see Table 1) should be present in the composition. This was desirable in order to capture the specific features linked to the various TAG categories [23,24]. Secondly, if a TAG comprised less than 1.5 % of the oil, the TAG was removed and the amount added to the most similar TAG included in the Although up to 3 % diacylglycerols were allowed in the oils, these were disregarded in the oil compositions.…”
Section: Lumping Of Oil Compositionsmentioning
confidence: 99%